1988
DOI: 10.1128/aem.54.3.760-767.1988
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of virulence factors and R plasmids of Salmonella spp. isolated from healthy and ill swine

Abstract: The antibiotic resistances and virulence profiles of Salmonella spp. isolated from healthy (group 1) and ill (group 2) swine were compared. Parameters studied included colicin and siderophore production; mannosesensitive hemagglutination of erythrocytes; resistance to the lethal effect of serum complement; resistance to antibiotics; and the transmissibility of these characteristics to recipient organisms. Group 1 (19 isolates) had 14 serotypes, and group 2 (20 isolates) had 2 serotypes. Isolates from group 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These classes of antimicrobial agents are normally administered to poultry in Greece either as therapeutic agents or in subtherapeutic doses in premixed form. As has been shown previously, such regimens increase the susceptibility to infections due to antimicrobial agent-resistant strains of Salmonella (24,29,30), thus aggravating the cost of potential treatment. Ampicillin resistance presents an additional problem not restricted to veterinary and food industry concerns, since, after 1991, the highest rates of resistance of human as well as animal isolates were to ampicillin.…”
Section: Discussionmentioning
confidence: 90%
“…These classes of antimicrobial agents are normally administered to poultry in Greece either as therapeutic agents or in subtherapeutic doses in premixed form. As has been shown previously, such regimens increase the susceptibility to infections due to antimicrobial agent-resistant strains of Salmonella (24,29,30), thus aggravating the cost of potential treatment. Ampicillin resistance presents an additional problem not restricted to veterinary and food industry concerns, since, after 1991, the highest rates of resistance of human as well as animal isolates were to ampicillin.…”
Section: Discussionmentioning
confidence: 90%
“…Our data showed that 35% Salmonella isolates ( n = 32) were positive for cib among 92 isolates examined [68]. Ability of colicin production may provide competitive colonization advantage to pathogen including Salmonella [69, 70].…”
Section: Discussionmentioning
confidence: 99%
“…Plates were incubated for 24 and 48 hours at 37 C and examined for growth around the wells. 13 Bacterial resistance to chicken complement-Chicken plasma was obtained from 7-week-old chickens that were negative for Salmonella antibodies.17 The lytic activity of chicken complement on the test organisms was monitored by the inoculation of 20 f-il of the test organism containing 5 x 106 colony-forming units into 1 ml of chicken plasma and 1 ml of heat-inactivated plasma (56 C for 30 minutes).17'18 Suspensions were placed in a quantitative, automated systemd and bacterial lysis or growth was recorded by changes in optical density every 15 minutes for 240 minutes.17 '18 Mannose-sensitive hemagglutination tests-The ability of the test strains to hemagglutinate erythrocytes was tested in 96-well round-bottom micro titration plates with a 3% suspension of guinea pig or chicken erythrocytes in a 0.85% NaCl solution. Combinations of 25 JJL!…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid screening-Plasmids were isolated from the test organisms by the method of Kado and Liu.20 Plasmid DNA was then analyzed by agarose gel electrophoresis. 13 Bacterial matings and selection of transconjugants-The R plasmids were transferred by mixing 0.2 ml of exponentially grown donor cells with 1.8 ml of an overnight culture of recipient cells in antibiotic medium 3e broth. Mixtures were incubated at 25 C, 37 C, and 42 C for 18 hours.…”
Section: Methodsmentioning
confidence: 99%